2014
DOI: 10.1021/bm500689g
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Degradation Properties and Biocompatibility of Amorphous and Functional Poly(ester-acrylate)-Based Materials

Abstract: Tuning the properties of materials toward a special application is crucial in the area of tissue engineering. The design of materials with predetermined degradation rates and controlled release of degradation products is therefore vital. Providing a material with various functional groups is one of the best ways to address this issue because alterations and modifications of the polymer backbone can be performed easily. Two different 2-methylene-1,3-dioxepane/glycidyl methacrylate-based (MDO/GMA) copolymers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Generally, the most common method to evaluate the copolymer degradation consists in following the decrease of the number‐average molecular weight ( M n ) with time. For example, Albertsson and co‐workers reported that MDO/glycidyl methacrylate (GMA) copolymers with a cumulative mole fraction of MDO units in the copolymer ( F MDO ) of 0.42 (synthesized with an initial MDO feed composition ( f MDO,0 ) of 0.65) lost 25% and 60% of their initial M n after 133 d of hydrolysis at 37 °C in PBS and deionized water, respectively. In the case of MDO/VA copolymers, Agarwal et al studied the hydrolytic degradation of copolymers with F MDO = 0.73 (synthesized with f MDO,0 = 0.76) in 5 wt% KOH methanol solution.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the most common method to evaluate the copolymer degradation consists in following the decrease of the number‐average molecular weight ( M n ) with time. For example, Albertsson and co‐workers reported that MDO/glycidyl methacrylate (GMA) copolymers with a cumulative mole fraction of MDO units in the copolymer ( F MDO ) of 0.42 (synthesized with an initial MDO feed composition ( f MDO,0 ) of 0.65) lost 25% and 60% of their initial M n after 133 d of hydrolysis at 37 °C in PBS and deionized water, respectively. In the case of MDO/VA copolymers, Agarwal et al studied the hydrolytic degradation of copolymers with F MDO = 0.73 (synthesized with f MDO,0 = 0.76) in 5 wt% KOH methanol solution.…”
Section: Introductionmentioning
confidence: 99%
“…They undergo radical and cationic ring-opening polymerization and provide polyesters, polyacetals or a combination of the two, depending on their structure and on the reaction conditions (12). 2-Methylene-1,3-dioxepane (MDO) is one of the very well studied CKAs in terms of homo-and copolymerization, with a large number of vinyl monomers such as methyl methacrylate (MMA) (13), styrene (14,15), vinyl acetate (16,17), propargyl acrylate (18), glycidyl methacrylate (GMA) (19), etc. Homopolymerization of MDO leads to an aliphatic biodegradable polyester with a polycaprolactone-like structure (20), whereas cationic polymerization of MDO provides mainly ring-retained acetal units in the polymer backbone (21).…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50][51] Poly(sulfides) provide an option for situations in which an oxidative response, such as those found in wound sites, is required 52, 53 and poly(disulfides) have potential application given the highly reducing environment found within cells compared to the systemic circulation. Poly(esters) or poly(amides), prepared by ring-opening polymerisation techniques, offer a route towards this where degradation by hydrolytic and/or enzymatic means is possible.…”
Section: (I) Triggering An "Isothermal" Response Via Backbone Modificmentioning
confidence: 99%